Comparison of Bypass and Non-Bypass Surgical Treatments for Internal Carotid Artery Blood Blister-Like Aneurysms: A Meta-Analysis of Efficacy, Safety, and Outcomes - Balik, Vladimir; Kourilova, Pavla; Sulla, Igor J; Vrbkova, Jana; Srovnal, Josef; Sulla, Igor; Talari, Sandeep (World neurosurgery, 2020)
BACKGROUND: The optimal surgical strategy for treating internal carotid artery (ICA) blood blister-like aneurysms (BBAs) has remained unclear. Although some have preferred bypass surgery, others have favored less-demanding surgical methods. The aim of the present meta-analysis was to assess the efficacy, safety, and outcomes of bypass and non-bypass surgical methods when intended as primary treatment of ICA BBAs. METHODS: Studies reporting data on the outcomes of interest for surgically treated patients with ICA BBAs were searched for in the PubMed/MEDLINE, Evidence-Based Medicine Reviews, Cochrane Central, ProQuest, and Scopus databases. The data were analyzed using random effects modeling. RESULTS: Seven observational studies involving 140 patients met the inclusion criteria. The patients treated with bypass surgery, compared with those treated with non-bypass techniques, had lower odds of poor outcomes (odds ratio [OR], 0.75; 95% confidence interval [CI], 0.28-2.02; P = 0.57; I2 = 0%), postoperative vasospasm (OR, 1.73; 95% CI, 0.38-7.92; P = 0.48; I2 = 19%), intraoperative bleeding (OR, 3.37; 95% CI, 0.82-13.90; P = 0.09; I2 = 0%), postoperative bleeding (OR, 1.91; 95% CI, 0.47-7.76; P = 0.36; I2 = 0%), and postoperative recurrence of BBAs (OR, 2.16; 95% CI, 0.54-8.66; P < 0.28; I2 = 0%). No comparison, however, achieved statistical significance. CONCLUSIONS: For surgeons who use both bypass and non-bypass surgical strategies, the 2 methods seemed comparable in terms of the outcomes of interest, although the bypass technique appeared superior. However, comparisons with studies reporting bypass as the uniquely preferred technique have indicated that specialization in, and preference for, the bypass procedure has been associated with more favorable outcomes.
Keywords: revaskularizace mozku; Humans; aneurysma; Surgical outcomes; Neurosurgical Procedures; Bypass surgery; Cerebral Revascularization; Meta-analysis; výsledek terapie; lidé; bezpečnost pacientů; Blood blister-like aneurysm; Internal carotid artery; Treatment Outcome; Patient Safety; Aneurysm; nemoci arterie carotis; Carotid Artery Diseases; neurochirurgické výkony